1996
DOI: 10.1111/j.1151-2916.1996.tb08993.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molybdenum Silicide Additions on High‐Temperature Oxidation Resistance of Silicon Nitride Materials

Abstract: The influence of additions of molybdenum disilicide (MoSi2) on the microstructure and the mechanical properties of a silicon nitride (Si3N4) material, with neodymium oxide (Nd2O3) and aluminum nitride (AIN) as sintering aids, was studied. The composites, containing 5, 10, and 17.6 wt% MoSi2, were fabricated by hot pressing. All materials exhibited a similar phase composition, detected by X‐ray diffractometry. Up to MoSi2 additions of 10 wt%, mechanical properties such as strength, fracture toughness, or creep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…[10][11][12][13][14][15] The improvement was attributed to the extensive formation of crystalline phases at the grain boundary. The high-temperature strength of Si 3 N 4 also was enhanced when fine SiC particles were added to make nanocomposite Si 3 N 4 -SiC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] The improvement was attributed to the extensive formation of crystalline phases at the grain boundary. The high-temperature strength of Si 3 N 4 also was enhanced when fine SiC particles were added to make nanocomposite Si 3 N 4 -SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the oxidation behavior of Si 3 N 4 sintered with various types of sintering additives. [1][2][3][4][5][6][7][8][9][10] When Si 3 N 4 is oxidized in air, SiO 2 is formed on the surface, which subsequently reacts with other oxides used as sintering additives, such as Y 2 O 3 or MgO, to form Y 2 Si 2 O 7 or MgSiO 3 , respectively. It also is widely accepted that the migration of additive cations, such as Y 3+ , Mg 2+ , or Ce 3+ , from the bulk grain-boundary region to the surface is an important step in determining the overall oxidation rate of Si 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in the temperature range 1200-1500 • C, MoSi 2 , assisted by oxygen, reacts with Si 3 N 4 forming Mo 5 Si 3 and additional Si 2 N 2 O and SiO 2 , that is the cause of the new rise of strength after the treatment at T ≥ 1200 • C. Thus the high level of strength retention in the range temperature 1200-1500 • C is expected, because of the high volume of [27][28][29] In fact, the present results show that the flexural strength of the oxidized specimens increases with the increase of the oxidation temperature. Otherwise, the presence of some porosity in the sub-oxide layer is due to the conversion MoSi 2 → Mo 5 Si 3 , as the silicide particles contract their volume: the high conversion occurring at 1500 • C leads to high porosity, that counterbalances the positive effect of the oxynitrides, decreasing the strength again.…”
Section: Long-term Oxidation and Properties Degradationmentioning
confidence: 88%
“…26 Oxidation and corrosion of non-oxide ceramic composites results in different behaviours and mechanisms depending on the temperature, besides the matrix microstructure and type and amount of the electroconductive particles. [18][19][20][21][22][23][24][25][27][28][29][30][31][32] In particular, chemical reactions leading to oxidation of silicon nitride or aluminium nitride matrices containing titanium nitride or molybdenum disilicide are accompanied by several diffusion phenomena, therefore, the complex interactions among the involved species at the reaction interface and inside the growing oxide scale and the development of complex product layers affect the overall oxidation behaviour. This paper shows the results of long-term oxidation and corrosion in aqueous basic or acid solutions on flexural strength and electrical resistivity of full dense composites in the systems: AlN SiC, AlN SiC MoSi 2 , Si 3 N 4 MoSi 2 and Si 3 N 4 TiN.…”
Section: Introductionmentioning
confidence: 99%
“…[8] MoSi 2 has been coupled to several ceramic matrixes, such as Si 3 N 4 , SiC, SiAlON, AlN and it has been found that its addition causes a significant improvement in the mechanical properties [9][10][11][12][13][14] and the oxidation resistance. [15][16] In this contribution, the microstructure and properties of SiC-based composites containing 10 and 30 vol% of MoSi 2 particulate are presented and compared to those of the reference SiC and MoSi 2 monolithic materials.…”
mentioning
confidence: 99%